Malaysian PLCs’ responses to survey: An indicator of CSR commitments - Janice L. H. Nga; Jonghyun Park (GRRI, 2018)
This article aims to examine corporate social responsibility (CSR) among Malaysian companies in particular public listed companies (PLCs). It examined CSR in reality vis-à-vis rhetorically via the research processes and responses received in a research. The experiences of the study from gaining access, communicating with the companies, and feedbacks at various stages had offered important aspects for further reflection. Aspects that may well be rhetorically explained and accepted as policy and rules may not necessarily been carried up at all levels, in this case the CSR aspect. As noted that all Malaysian PLCs have got a CSR statement and/or policy, as well as making CSR reporting a compulsory content in PLCs, the consideration of commitments varied at different levels. Hence, it is time to reflect whether PLCs are doing CSR to their advantages as such for publicity and/or tax exemption in which neither of them were offered through answering the questionnaire. It did not reflect the willingness or CSR of targeted companies in ‘helping’ and ‘doing good’ by answering the survey questions that all the people approached in the study agreed that such study will do good to the society through sharing knowledge to improve the environment quality. While the measurement of CSR shall be undoubtedly revisited and to be more defined, an important question, however debatable, will be ‘is CSR for civility or it is a business good?’ that certainly need further investigation for better explanation and clarification of corporate social responsibility.